EFFICIENCY IN INDIA: AN EMPIRICAL STUDY OF PUBLIC AND PRIVATE SECTOR - Mittal, Palak; Singh, Ravi Inder (Gyan Management Journal, 2024)
This study delves into the Total Factor Productivity (TFP) growth of major Indian private and public sector banks from 2012 to 2022, employing the Malmquist Productivity Index and Data Envelopment Analysis (DEA). It scrutinizes TFP change, technical change, and efficiency change within the banking sector. Among public sector banks, approximately 58% exhibit positive productivity changes, contrasting with the increased productivity of private banks displaying 31.5%. Significant differences in TFP become evident, with Canara Bank ranking highest among public sector banks, achieving a TFP score of 1.059, while Punjab National Bank exhibits the lowest TFP, averaging at 0.948. In the private sector, Axis Bank emerges as the frontrunner with an average TFP of 1.145, whereas Tamil Nadu Mercantile Bank lags behind with an average TFP of 0.381. These findings furnish policymakers and stakeholders with crucial insights to formulate strategies aimed at bolstering the technical efficiency of both private and public sector banks in India, significant for the sector’s sustained growth and stability.